Morphological variability may limit single-cell specificity to electric field stimulation - Trotter, Daniel; Pariz, Aref; Hutt, Axel; Lefebvre, Jérémie (Frontiers in Synaptic Neuroscience, 2025)
IntroductionNon-invasive brain stimulation techniques, widely used to manipulate neural excitability and behavior, are well studied at the meso- and macroscopic scales. However, less is known about their specificity at the level of individual cells.MethodsModels based on real pyramidal and parvalbumin neuron morphologies created by the Allen Institute for Brain Science were characterized using metrics we devised to quantify various aspects of cellular morphology, ranging from whole cell attributes to net compartment length, branching, diameter and orientation. The models were simulated to quantify the single-cell variability and evoked response susceptibility to uniform electric fields.Results and discussionNo physical traits yielded layer- or cell-type-specific responses passing statistical significance tests. While uniform electric fields reliably modulated somatic, dendritic and axonal compartments, and subtype-specific responses were observed, specificity was blurred by the variability in cellular morphology. These null results suggest morphology alone may not account for the reported subtype specificity to electric field stimulation, and question the extent to which non-invasive techniques can control specific components of neural circuitry.